Creating livable cities regional perspectives. - Asian Development Bank. (Metro Manila, Philippines Asian Development Bank, 2019)
Urbanization is creating new opportunities to stimulate innovation, boost economic development, and transform human well being. Across the world, cities are looking to evolve from traditional centers of economic activity to become engines of green and inclusive growth. However, in developing and emerging economies, cities are often constrained by underinvestment in infrastructure and services as well as inadequate urban governance, planning, and financing frameworks. This publication takes stock of urbanization and urban development patterns in developing and emerging economies. It also examines the policy interventions needed to promote competitive, inclusive, equitable, environmentally sustainable, and climate resilient cities in short, livable cities.
Keywords: Economic development; Public administration; Urbanization; Electronic books